The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Continental‐scale analysis of feral cat diet in Australia, prey‐switching and the risk: benefit of rabbit control - Greg Mutze (Journal of Biogeography, 2017)
Recent analyses of geographical variation in cats’ diet across Australia have been used to highlight rabbit control as a conservation risk, on the basis that prey‐switching by cats following rabbit control is likely to threaten Australian fauna. There is no direct evidence to support that proposition. However, there is direct evidence of repeated prey‐switching due to seasonal fluctuations in uncontrolled rabbit populations, of long‐term suppression of rabbit numbers by effective rabbit control, and that reduced rabbit abundance leads to reduced cat abundance, reduced predation of native fauna and recovery of threatened prey populations. Furthermore, rabbits are a known threat to many Australian native plants and rabbit control has proven benefits for their recovery, thereby offering long‐term benefits for dependent fauna and broader ecosystem function. On the balance of evidence, rabbit control should be encouraged in Australia wherever possible, as a national conservation priority.

Density-dependent grazing impacts of introduced European rabbits and sympatric kangaroos on Australian native pastures - Greg Mutze; Brian Cooke; Scott Jennings (Biological Invasions, 2016)

Environmental effects and individual body condition drive seasonal fecundity of rabbits: identifying acute and lagged processes - Konstans Wells; Robert B. O’Hara; Brian D. Cooke; Greg J. Mutze; Thomas A. A. Prowse; Damien A. Fordham (Oecologia, 2016)

Molecular epidemiology of R abbit H aemorrhagic D isease V irus in A ustralia: when one became many - John Kovaliski; Ron Sinclair; Greg Mutze; David Peacock; Tanja Strive; Joana Abrantes; Pedro J. Esteves; Edward C. Holmes (Molecular Ecology, 2014)
R abbit H aemorrhagic D isease V irus ( RHDV ) was introduced into A ustralia in 1995 as a biological control agent against the wild E uropean rabbit ( O ryctolagus cuniculus ). We evaluated its evolution over a 16‐year period (1995–2011) by examining 50 isolates collected throughout A ustralia, as well as the original inoculum strains. Phylogenetic analysis of capsid protein VP 60 sequences of the A ustralian isolates, compared with those sampled globally, revealed that they form a monophyletic group with the inoculum strains ( CAPM V‐351 and RHDV 351 INOC ). Strikingly, despite more than 3000 rereleases of RHDV 351 INOC since 1995, only a single viral lineage has sustained its transmission in the long‐term, indicative of a major competitive advantage. In addition, we find evidence for widespread viral gene flow, in which multiple lineages entered individual geographic locations, resulting in a marked turnover of viral lineages with time, as well as a continual increase in viral genetic diversity. The rate of RHDV evolution recorded in A ustralia −4.0 (3.3–4.7) × 10 −3 nucleotide substitutions per site per year – was higher than previously observed in RHDV , and evidence for adaptive evolution was obtained at two VP 60 residues. Finally, more intensive study of a single rabbit population (Turretfield) in S outh A ustralia provided no evidence for viral persistence between outbreaks, with genetic diversity instead generated by continual strain importation.

Damage caused by low-density exotic herbivore populations: the impact of introduced European rabbits on marsupial herbivores and Allocasuarina and Bursaria seedling survival in Australian coastal shrubland - Peter Bird; Greg Mutze; David Peacock; Scott Jennings (Biological Invasions, 2012)

Rabbit Haemorrhagic Disease: Applying Occam’s Razor to competing hypotheses - DAVID PEACOCK; GREG MUTZE; RON SINCLAIR; JOHN KOVALISKI; BRIAN COOKE (Molecular Ecology, 2012)
Rabbit haemorrhagic disease virus (RHDV) is a highly virulent lagovirus endemic in Europe and Australasian populations of the European rabbit, Oryctolagus cuniculus . It has also caused several unexplained disease outbreaks in domestic European rabbits in North America. Non‐pathogenic spread of RHDV leading to persistent infection which later reactivated has recently been proposed as the cause of overt disease and death of a pet rabbit in Canada, the first confirmed case of Rabbit haemorrhagic disease in that country. We suggest that there is little evidence to support non‐pathogenic spread of virulent RHDV, some evidence that is contradictory, and evidence to support a simpler alternative hypothesis. RHDV can be spread over long distances between sparse rabbit populations by fomites or flying insects. Although highly pathogenic, RHDV can be limited in its spread within rabbit populations, or its presence masked by closely related but non‐pathogenic lagoviruses which can provide protection against acute disease. In the absence of any evidence from clinical studies to support reactivation of persistent RHDV infection, the simpler explanation seems more likely to be correct.